Implementing the European Pillar of Social Rights: what is needed to guarantee a positive social impact - Sabato, Sebastiano; Ghailani, Dalila; Peña-Casas, Ramón; Spasova, Slavina; Vanhercke, Bart (Brussels, 2018)
"This new study on behalf of the Workers’ Group of the EESC concludes that the Pillar relaunched an ambitious EU ‘Social Agenda’ and has already influenced the 2018 European Semester cycle. However, doubts remain as to whether it can influence EU macro-economic and fiscal policies. National trade unions are doubtful that they will be involved in putting its principles into practice. Effective implementation requires that the Pillar be given adequate financial resources and clearly defined governance tools through an ambitious roadmap."